2017
DOI: 10.1007/s40974-017-0060-0
|View full text |Cite
|
Sign up to set email alerts
|

How well are we managing E-waste in India: evidences from the city of Bangalore

Abstract: As a toxic waste stream, E-waste poses serious challenges to the waste management initiatives in India. While the hazardous components of E-waste call for environment-friendly disposal mechanisms, the valuable and precious metal constituents necessitate adequate infrastructural provisions and responsible management programmes to avoid the loss of economically vital materials. Considering this duality, this paper is an attempt to evaluate the current E-waste disposal practices in India, particularly emphasizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…For example, due to some financial incentives involved, Indian consumers are willing to sell their obsolete e-waste to the "kawariwalas" (doorto-door scrap collectors). This behaviour is totally different from practices adopted by most developed countries whereby the producers and consumers have to pay "Recycling/Disposal Fee" [62][63][64].…”
Section: Indiamentioning
confidence: 79%
“…For example, due to some financial incentives involved, Indian consumers are willing to sell their obsolete e-waste to the "kawariwalas" (doorto-door scrap collectors). This behaviour is totally different from practices adopted by most developed countries whereby the producers and consumers have to pay "Recycling/Disposal Fee" [62][63][64].…”
Section: Indiamentioning
confidence: 79%
“…CBOs seek to organize localized groups of informal dismantlers in each area. This may be done by using cutting-edge co-working models as employed by local organizations in the study area, and by offering them secure, healthy, and legal workspaces [19]. As a result, integration with the official sector is made possible.…”
Section: Formalizing the Informal From Within Community-based Organis...mentioning
confidence: 99%
“…They suggested that the circular economy concept can influence the socio-economic culture and promote green practices. However, Borthakur and Govind (2017) argued that in developing countries like India, various factors like socio-cultural, economic, political, technological, infrastructural and environmental differences play a pivotal role in public acceptance of e-waste policy.…”
Section: Implications Of the E-waste Collection Policymentioning
confidence: 99%